Antifungal Activity of Crude Extracts of Some Medicinal Plants against Fusarium solani (Mart.) Sacc. - Shrestha, Asha Kaji; Tiwari, R. D. (Ecoprint: An International Journal of Ecology, 2010)
The crude extracts of six plants viz, Allium sativum, Capsicum annuum, Artimesia vulgaris, Eupatorium adenophorum, Gaultheria fragrantissima and Phyllanthus emblica were assessed in vitro for activity against fungi Fusarium solani (Mart.) Sacc., the causal agent of dry potato tuber rot. Pathogenecity test was confirmed by inoculating the pathogen into the healthy potato tuber. The assessment of fungitoxicity was carried out by poisoned food technique using ten different concentrations (10, 20, 30, 40, 50, 60, 70, 80, 90 and 100%) against the test fungus. Assessment was carried out in terms of percentage of mycelial growth inhibition of the test fungus. The extracts of all the plant species were found to be effective in inhibiting the mycelial growth. The extract of A. sativum completely inhibited the mycelial growth of the test fungus at the concentration of 40% and the extracts of Capsicum annuum and Phyllanthus emblica inhibited the mycelial growth completely at the concentration of 100%. Key words: Plant extracts, antifungal activity. DOI: 10.3126/eco.v16i0.3476 ECOPRINT 16: 75-78, 2009